Synthesis and Characterization of Se4+@TiO2/PET Composite Photocatalysts with Enhanced Photocatalytic Activity by Simulated Solar Irradiation and Antibacterial Properties - Yu Ren; Rui Luan; Ziyao Zhao; Lina Tang; Chunxia Wang; Yuehui Li; Meixian Li (Molecules)
To fabricate recyclable catalytic materials with high catalytic activity, Se4+@TiO2 photocatalytic materials were synthesized by the sol–gel method. By introducing free radicals on the surface of polyester (PET) fabrics through plasma technology, Se4+@TiO2/PET composite photocatalytic materials with high photocatalytic activity were prepared. The surface morphology, crystal structure, chemical composition, and photocatalytic performance were characterized by scanning electron microscopy (SEM), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), ultraviolet–visible absorption spectroscopy (UV–Vis), and photoluminescence spectroscopy (PL), respectively. The photocatalytic degradation performance was determined by assessing the degradation of azo dye methyl orange under simulated solar irradiation. The results demonstrated that Se4+@TiO2/PET exhibited a superior degradation rate of methyl orange, reaching up to 81% under simulated sunlight. The PL spectra indicated that the electron–hole pair separation rate of Se4+@TiO2/PET was higher than that of TiO2/PET. Furthermore, UV–Vis spectroscopy demonstrated that the relative forbidden band gap of Se4+@TiO2/PET was determined to be 2.9 eV. The band gap of Se4+@TiO2/PET was narrower, and the absorption threshold shifted toward the visible region, indicating a possible increase in its catalytic activity in simulated solar irradiation. In addition, the antibacterial properties of Se4+@TiO2/PET were subsequently investigated, achieving 99.99% and 98.47% inhibition against S. aureus and E. coli, respectively.